Biomimicked and CPMV-Imprinted Hollow Porous Zinc Phosphate Nanocapsules and Their Therapeutic Efficiency - Kumar K.; Paik P. (My University, 2025)
Hollow zinc phosphate nanocapsules (hZPNCs) are an alloplastic biomaterial that has been synthesized to deliver chemotherapeutic drugs in a sustained manner. A very simple one-pot synthesis approach has been employed to synthesize hZPNCs by using cowpea mosaic virus (CPMV) in the presence of phosphate buffer (PBS) (0.01 M PBS, pH ∼7.2) with zinc acetate precursor. The synthesis mechanism of hZPNCs relies on the basis of biomineralization, where the precursor molecules initiate mineralization with the help of amino acid residues present on the CPMV capsid. The synthesized hollow nanocapsules were of diameter ∼50-60 nm and porous shell with thickness of ∼4 nm. The cavity performed as a reservoir for the anticancer drugs (DOX and IM). The release kinetic studies show the positive aspect of hZPNCs to be labeled as drug delivery cargo for sustained delivery. In vitro cytotoxic studies of hZPNCs and hZPNCs-chemo drugs on HEK293, HEPG2, and K562 cells were performed. The cytotoxic studies show that hZPNCs-DOX and hZPNCs-IM arrest the cell cycle of carcinoma cells (HEPG2 and K562 cells) at relatively low IC50 and that the inhibition efficiency is dosage dependent. Furthermore, through HRTEM, in vitro cellular interactions of carcinoma cells with hZPNCs and chemo drug-loaded hZPNCs were confirmed by the cryo-sectioning of cells before and after the incubation. These studies revealed the likely endocytic pathway for the nanocapsules entering the cell and executing the specific action of delivering the anticancer drugs. Together, these results reveal the hZPNCs as potential sustained drug delivery agents. © 2020 American Chemical Society.